EVALUASI SISTEM PENGENDALIAN INTERNAL PADA SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG HABIS PAKAI (STUDI KASUS PADA HOTEL X) - Silmi Fitriana; Miswaty Miswaty; Hairul Anam (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
The development of the capital city of the archipelago, which is located in East Kalimantan, has attracted a lot of attention, so many people come for business purposes or other reasons. This has a positive impact on economic activities, one of which is the hotel industry. Hotel is a service company that provides accommodation services to tourists. One way to maximize hotel operational strategies is by paying attention to everything related to guest service, one of which is managing the inventory of guest supplies. Guest supplies are equipment provided by the hotel as a complement to services to ensure comfort during guests' stay. An internal control system in the consumable goods inventory accounting information system is needed by the company in order to assist management in increasing the effectiveness and efficiency of the company to avoid the risk of fraud, differences in existing physical stock with the system and produce user-relevant information. The purpose of this research is to evaluate the application of the internal control system to the consumable goods inventory accounting information system at the Hotel X Balikpapan. This research uses the five COSO internal control components in assessing the effectiveness of the internal control system for out-of-stock inventory at the Hotel X Balikpapan. The method used is qualitative research with a case study design. The type of data used is data obtained from questionnaires, interviews and observations. The results of the research show that the internal control system for the accounting information system for inventory of consumables implemented by Hotel X Balikpapan is adequate, however there are still discrepancies found in the components of control and monitoring activities. The results of this research can be used as a basis for improving internal control in companies so that in the future there are no irregularities